Dynamic Comovement between Indian Commodity Futures, Economic Policy Uncertainty and Geopolitical Risk: Evidence from Wavelet Analysis - Thilaga, M.; Rajkumar, K. Prabhakar (International Journal of Economics and Financial Issues, 2024)
The present study examines the dynamic comovements between two global risk factors and commodity futures returns. The study considers the daily futures price of nine commodities spanning from January 4th, 2012 to September 29th, 2023. The study employs wavelet analysis and wavelet- based Granger causality tests to analyze dynamic comovement and causal relationship between global risk factors and commodity futures return at different time horizons. The study results show a strong comovement between the US economic policy uncertainty (USEPU) and commodity futures return except for silver and mentha oil. On the other hand, the geopolitical risk (GPR) exhibits a weak relationship with gold, lead, zinc, and energy commodities across all-time frequencies. Further, the Wavelet Granger causality test results provide strong evidence that commodities futures return cause the USEPU in all the time horizons. Followed by the geopolitical risk reports significant evidence that commodities futures return causes GPR in all time horizons.